TECHNIQUE MUHASABAH TO ADDRESS INNER CHILD IN STUDENTS - Bancin, Wahdaniati; Lubis, Ramadhan (FORUM PAEDAGOGIK, 2025)
This study aims to explore the application of the muhasabah technique as a psychospiritual approach in dealing with the inner child in grade XII Aliyah students at the Al-Jam’iyatul Washliyah Brayan Orphanage in Medan. The inner child is a part of the personality that is formed from unresolved childhood experiences, which can have a negative impact on a person's emotional and social development in adolescence and adulthood. The muhasabah approach was chosen because it combines elements of psychological reflection and Islamic spiritual values as a means of emotional recovery.  This study uses a qualitative method with a case study approach, involving participatory observation, in-depth interviews, and documentation. The subjects of the study consisted of grade XII students, spiritual guidance teachers, and orphanage supervisors. The results of the study indicate that the practice of muhasabah plays an important role in helping students identify, understand, and heal childhood emotional wounds. This process occurs through spiritual lectures, reflective activities after worship, and personal interactions that build emotional awareness and spiritual closeness. The technique of muhasabah, although not done formally, The findings that the practice of muhasabah has a significant contribution in forming inner peace, managing emotions more stably, and encouraging the growth of students' spiritual maturity.